2023
DOI: 10.3390/md21040229
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Nanostructure of Myristoylated ω-Conotoxin MVIIA Increases the Duration of Efficacy and Reduces Side Effects

Abstract: Chronic pain is one of the most prevalent health problems worldwide. An alternative to suppress or alleviate chronic pain is the use of peptide drugs that block N-type Ca2+ channels (Cav2.2), such as ω-conotoxin MVIIA. Nevertheless, the narrow therapeutic window, severe neurological side effects and low stability associated with peptide MVIIA have restricted its widespread use. Fortunately, self-assembly endows the peptide with high stability and multiple functions, which can effectively control its release to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, there was no significant difference in the improvement of serum stability between single-site and two-site modification. Comparison with previous work showed that both acylated and alkylated peptides self-assembled to form micelles, improving the serum stability of the peptides (Ding et al 2023 ). This work provides a technical basis for the alkyl chain modification of peptide MVIIA, and the assembly of peptides into micelles will also provide a structural basis for its further study.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, there was no significant difference in the improvement of serum stability between single-site and two-site modification. Comparison with previous work showed that both acylated and alkylated peptides self-assembled to form micelles, improving the serum stability of the peptides (Ding et al 2023 ). This work provides a technical basis for the alkyl chain modification of peptide MVIIA, and the assembly of peptides into micelles will also provide a structural basis for its further study.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, it is shown that alkyl chain length and spatial exclusion between alkyl chains in the hydrophobic core limit the size and shape of nanospheres formed by peptide self-assembly (Muthusivarajan et al 2020 ). Nanostructures formed by peptide self-assembly are believed to be effective in improving peptide stability, increasing resistance to enzymatic degradation, prolonging the half-life of peptide drugs, and reducing drug side effects (Ding et al 2023 ; Zhou et al 2017 ; Gao et al 2023 ). Many approved fatty acid chain modification (similar to alkyl chain modification) drugs are in clinical use, and the fatty acids commonly used for drug modification are mainly myristic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Borneol (BOR)-modified Liposomes (LIPs) were membrane fused with exosome Microneedles (MNs) in an animal study provided a safe and effective administration of chronic pain treatment by improving the ability of ziconotide across the BBB [ 133 ]. Myristoylated N-terminal ziconotide can undergo self-assembly onto micelles, resulting in extended analgesic effects and a notable reduction in the risk of side effects such as tremors and impaired motor coordination in mice [ 104 ]. Numerous patents have been filed to theoretically modify ziconotide's structure to enhance its ability to cross the BBB, but none of these modifications have been validated in humans or made commercially available [ 128 , 134 ].…”
Section: Future Prospectivementioning
confidence: 99%